Predictors of Outcomes in Autism Early Intervention: Why Don’t We Know More? - Vivanti, Giacomo; Prior, Margot; Williams, Katrina; Dissanayake, Cheryl (Frontiers in Pediatrics, 2014)
Response to early educational treatment programs in autism is variable. However the factors associated with positive versus poor treatment outcomes remain unknown. Hence the issue of which intervention/s should be chosen for an individual child remains a common dilemma. We argue that lack of knowledge on “what works for whom and why” in autism reflects a number of issues in current approaches to outcomes research, and we provide recommendations to address these limitations. These include: a theory-driven selection of putative predictors; the inclusion of proximal measures that are directly relevant to the learning mechanisms demanded by the specific educational strategies; and the consideration of family characteristics. Moreover, all data on associations between predictor and outcome variables should be reported in treatment studies.